1999
DOI: 10.1046/j.1440-1819.1999.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression among caregivers of the disabled elderly in southern Japan

Abstract: The present study was conducted in an attempt to investigate factors related to depression of caregivers who looked after the disabled elderly residing in a community in southern Japan. A questionnaire survey was carried out of 45 pairs of caregivers and the disabled elderly who received regular visits from a practice nurse, who was located in Onga County, Fukuoka, in southern Japan. Twenty-four out of 45 caregivers (53.3%) scored above the conventional cut-off of the Center for Epidemiologic Studies Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Factors related to the successful group Our longitudinal study showed that the prevalence of dementia among the elderly was higher and that behavioural disturbances were more severe in the unsuccessful group, which is consistent with many other cross-sectional studies that have shown a positive relationship between the burden or depressive symptoms of the caregiver and the behavioural disturbances associated with dementia [7,11,[27][28][29][30][31]. In addition, caregivers spent a significantly longer time caregiving and attending the elderly in the unsuccessful group, which is also consistent with previous findings [7,[10][11][12][13].…”
Section: Discussionsupporting
confidence: 89%
“…Factors related to the successful group Our longitudinal study showed that the prevalence of dementia among the elderly was higher and that behavioural disturbances were more severe in the unsuccessful group, which is consistent with many other cross-sectional studies that have shown a positive relationship between the burden or depressive symptoms of the caregiver and the behavioural disturbances associated with dementia [7,11,[27][28][29][30][31]. In addition, caregivers spent a significantly longer time caregiving and attending the elderly in the unsuccessful group, which is also consistent with previous findings [7,[10][11][12][13].…”
Section: Discussionsupporting
confidence: 89%
“…We conducted two cross‐sectional studies on depression in caregivers. 8,9 These studies were conducted in rural towns. In our previous studies, the depressed caregivers used significantly less formal services 8 and took care of the frail elderly with more behavioral disturbances 9 than the non‐depressed caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore difficult to identify the impact of respite in the context of these many confounding interventions. Of the studies examining general service use, four failed to show an association of service use with carer depression; 121,128,129,131 one showed a negative effect Depression significantly lower with immigrant carer helper Home + ADC, adult day care. a +, positive effect of respite; 0, no effect of respite; -, negative effect of respite.…”
Section: Provision Of General Servicesmentioning
confidence: 96%
“…91,96,98,106,116,131 Two studies reported a positive effect of service use on burden 91,116 and four no effect. 96,98,106,131 Of the two studies finding a positive effect of service use, the study by Arai et al 91 was small, having only 24 participants, and thus gives little weight to the evidence. Lechner 116 also demonstrated a positive effect of service use.…”
Section: Provision Of General Servicesmentioning
confidence: 99%
See 1 more Smart Citation